Slope stability analysis in various Terraces model (case study: Sendangmulyo, Tirtomulyo District, Wonogiri Regency). Issue 1 (April 2021) - Surjandari, Niken Silmi; Fitri, Siti Nurlita; Purwana, Yusep Muslih; Prakosa, Brilian Budi; Djarwanti, Noegroho; Setiawan, Bambang; Dananjaya, Harya; Saido, Agus P
Abstract: Wonogiri has various contours. Steep slopes dominate some areas. Hence it has a high possibility to occur landslides. There are still a lot of people living under the slopes. Therefore, this research is essential for disaster mitigation purposes. The study aims to know how the value of the slope safety factor changes with construction terraces design. The research was conducted by collecting secondary data and improving the Terraces construction carried out. The data was analyzed in the limit equilibrium method to provide conditions before and after the rain. The models were tried with several Terraces variations on the slope to obtain the most optimal design. The results used a simplified Bishop method. The design of terraces on the slopes of Sendangmulyo Wonogiri Village shows that the SF value increase is only for the conditions before a rain. In contrast, the states after the rain do not yield a safety condition. The SF value increases if the number of steps increases, whereas the more step height increases, the less the SF value will be.